Multiple Solutions for Nonlinear Navier Boundary Systems Involving (p1(x),…,pn(x))-Biharmonic Problem - Qing Miao (Discrete Dynamics in Nature and Society)
We improve some results on the existence and multiplicity of solutions for the (p1(x),…,pn(x))-biharmonic system. Our main results are new. Our approach is based on general variational principle and the theory of the variable exponent Sobolev spaces.